A measuring method of standard resistance and analysis of measuring results. (December 2021) - Guan, Zexin; XinyanWang, Mei Yang; Li, Wenqiang; Sun, Xiaoyan; Wang, Dalong; Wang, Shang
Abstract: DC standard resistance is widely used in precision measurement, verification, traceability and other fields due to its high accuracy and good stability. First-class resistance standard has used to measure it based on the bridge turn equilibrium principle. According to JJF1059.1–2012 Evaluation and expression of uncertainty in measurement, the uncertainty of measurement results has been evaluated on uncertainty of the transfer standard, the basic error, sensitivity, load power, tank temperature, thermoelectric power and staff. This paper analyzes the uncertainty of the measurement results which will useful to measurement uncertainty assessment of standard resistance in future testing work.